Collective Landscapes. The Gran Consortile di Riclaretto and Collective Property in the Germanasca Valley - Michele Francesco Barale; Margherita Valcanover (Revue de Géographie Alpine)
Communal land management is a core element of the Alpine mountain landscape. In the Germanasca Valley, situated in Italy’s Turin region, collective management in the form of private shared ownership has been taking place for centuries.This study, perhaps the first of its kind in this particular geographical area, seeks to sketch a picture of these proprietary structures and bring out their salient features by investigating the value of these realities today. This type of shared ownership is described with regard to location, property and use rights, land and landscape use and its economic dimension. The last point of focus is two recently established land associations (As.Fo.) located on the same axis of collective management.While some properties are still being used as they were originally intended, others remain only on paper, and others have been lost to history. Among these collective properties, the case of the Gran Consortile di Riclaretto in Perrero stands out as a property that has managed to virtuously transform its use by adapting to the current dynamics.Archival sources and oral interviews form the basis for this research, which was conducted with an eye on the passage of history and by analysing the territory and the landscape. This paper investigates the meaning of Riclaretto for neighbouring properties but with a strategic view towards the future of the mountain environment itself.